The development of local currency bond markets and uncovered interest rate parity - Cyn-Young Park; Kwanho Shin (Asian Development Bank (ADB), 2023)
This paper investigates whether the uncovered interest parity (UIP) will hold more firmly if the local currency bond markets (LCBMs) are more developed, and the presence of nonbank financial institutions (NBFIs) is expanded. Deviations in UIP decrease as LCBMs develop, while the patterns of the UIP premium in emerging markets increasingly resemble patterns in advanced economies. Capital flows respond more sensitively to the UIP premium for emerging markets when LCBMs are more developed. These suggest the development of LCBMs and NBFIs might induce more active cross-border carry trades and reduce UIP deviations. However, greater carry trade positions may increase a country's exposure to market disruptions and exchange rate volatility. Empirical results show that gross portfolio debt inflows increase (decrease) when the exchange rate appreciates (depreciates). While LCBMs becoming more developed can mitigate the negative effect of the original sin redux hypothesis in advanced economies, this aggravates the impact of exchange rate depreciation in emerging markets.
Keywords: E44; F34; F62; G12; G21; G23; 330; uncovered interest parity; local currency bond markets; emerging economies; nonbank financial institutions; capital inflows